Edifícios de alto padrão e as estratégias de venda dos agentes imobiliários : um estudo de casos : Ecoville (Curitiba-PR) e Gleba Palhano (Londrina-PR) - Silva, Andresa Lourenço da (2014)
In this thesis was analyzed the production of urban space from the high standard vertical condominiums, specifically in Ecoville (Curitiba-PR) and Gleba Palhano (Londrina-PR) in the last decade (2001-2011). The term "high standard" was defined from three determinant elements such as location, standard of construction and "club style". However, other qualities, secondarily, also serve to define it. The thesis argues that it in both "neighborhoods", the high standard buildings resulted from processes in which are found some similar features in the spatial configuration, as the consumer market and the builders and developers. The distinguishing features relate to the size of the private area of the apartment, the size of the terrains, the prices of apartments and builders and developers that are both publicly held as privately held. The adopted methodology was qualitative exploratory research (with case studies), that involved bibliographic and documental survey, readings, critical analysis of selected works for study and semi-structured interviews with residents of the buildings in Curitiba and Londrina. Thus, it is concluded that the high standard buildings in Ecoville and Gleba Palhano are inserted in different urban and social realities, but they have some similarities and approaches in the models of habitation for the group with high purchasing power.